2003
DOI: 10.1002/esp.432
|View full text |Cite
|
Sign up to set email alerts
|

Recent ventifact development on the central Oregon coast, western USA

Abstract: The unusual location of ventifacts, on a boulder-built jetty at the mouth of the Siuslaw River, Oregon coast, western USA, allows ventifact age and wind abrasion rates to be estimated with some precision. The jetty was built mainly between 1892-1901 and extended throughout the twentieth century. Consideration of historical shoreline position and the history of jetty construction and repair suggests the ventifacts have formed since about 1930.Morphologically the ventifacts are aligned south-to-north reflecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Based on laboratory experiments, Kuenen (1960) concluded that ventifacts would develop very slowly where only fine sand is available (one to two centuries), quickly with medium sand (a few dozen years) and very rapidly on stormy beaches (a few dozen years). This latter conclusion is consistent with observations of Knight and Burningham (2003), who concluded that ventifacts along the Oregon coast, abraded by medium-grained, well-sorted sands, have a maximum age of 60-70 years. Rates of 0.24-1.63 mm/yr were calculated for this site.…”
Section: Rates Of Abrasionsupporting
confidence: 82%
See 1 more Smart Citation
“…Based on laboratory experiments, Kuenen (1960) concluded that ventifacts would develop very slowly where only fine sand is available (one to two centuries), quickly with medium sand (a few dozen years) and very rapidly on stormy beaches (a few dozen years). This latter conclusion is consistent with observations of Knight and Burningham (2003), who concluded that ventifacts along the Oregon coast, abraded by medium-grained, well-sorted sands, have a maximum age of 60-70 years. Rates of 0.24-1.63 mm/yr were calculated for this site.…”
Section: Rates Of Abrasionsupporting
confidence: 82%
“…Aggregated grains tend to plaster against the target, creating mass gain rather than loss. Field studies of target materials and sand-abraded rocks indicate a mass loss of between 30 and 1630 µm/yr (Sharp, 1964(Sharp, , 1980Greeley et al, 1984;Kuenen, 1960;Knight and Burningham, 2003). High-speed video (HSV) experiments help to elucidate the process, demonstrating that: (a) the windward side of rocks are subject to abrasion, (b) sand hits the targets directly and is not deflected by vortices that affect dust, (c) the outgoing particle velocity is less than the incoming, showing that kinetic energy is transferred to the target surface (Banks, Bridges and Benzit, 2005;Laity and Bridges, 2009), and (d) some grains rebound into the airstream and therefore provide a second impact to the surface, amplifying the abrasion .…”
Section: Mass Loss By Sand Abrasionmentioning
confidence: 99%
“…This is in contrast to field studies of sand-abraded rocks and other targets in which values of 30-1630 µm yr − 1 were measured (Sharp, 1980;Malin, 1985;Knight and Burningham, 2003). The only dust investigations are for industrial applications under conditions different than those in the field.…”
Section: Abrasion By the Impact Of Dust And Sandmentioning
confidence: 93%
“…This period was also likely associated with coastal ventifact formation as a result of this increased wind and storm activity (Braley and Wilson, 1997;Knight and Burningham, 2001;Wilson et al, 2002b). The fresh appearance and absence of lichen overgrowth on ventifacted surfaces in Gweebarra Bay suggests strongly that ventifaction occurs to the present-day, and therefore that wind-blown sand is an active geomorphic agent on paraglacial coasts (Knight, 2003;Knight and Burningham, 2003). This contrasts with some other coastal settings in the British Isles where ventifacts may be largely relict features (Table 2).…”
Section: Age Of Ventifactionmentioning
confidence: 54%
“…Relationships between reconstructed wind direction and facet/keel orientation on fossil ventifacts can be confirmed with reference to ventifacts forming in modern settings with known wind regimes (e.g. Knight, 2003;Knight and Burningham, 2003). These studies suggest, therefore, that there is a firm methodological footing for interpretation of past wind regimes based on ventifact morphology, which also has implications for palaeogeography, wind strength, positioning of high pressure cells and the location of sand sources and sinks.…”
Section: Introductionmentioning
confidence: 75%